Acoustic CO2 Gas Sensor Based on Phase Difference Measurement - Melany Febrina; Eko Satria; Mitra Djamal; Wahyu Srigutomo; Martin Liess (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2021)
In this research, an acoustic sensor has been successfully built to measure the concentration of CO2 gas in a mixture of gases (N2 and CO2). The nitrogen and carbon dioxide gases used are ultra-high purity (UHP) gas. The measurement parameter used is the speed of sound by utilizing the phase shift between ultrasonic wave signals that are sent and received continuously. The acoustic method in this research is by using the speaker as an ultrasonic wave transmitter, and the microphone as an ultrasonic wave receiver emitted by the speaker on the gas medium. This acoustic phase shift method is very sensitive to be used to determine the speed of sound on a gas medium. From the sensor testing, the sensor has good linearity in detecting changes in CO2 concentration in the gas mixture. The sensor test results have been validated theoretically and obtained an RMS error of 3.36 (3.36% with a maximum concentration of 100%), this proves that the work of the sensor is in accordance with the theory. In addition to theoretical validation, the work of the sensor has also been validated by looking at the direct relationship between sensor input and output through the inverse function, and an RMS error of 3.51 (3.51% with a maximum concentration of 100%) is obtained. From the overall results obtained, the acoustic CO2 gas sensor that is built can detect changes in CO2 concentrations in the gas mixture accurately, fabrication of the sensor is easy to do, and the costs required in the manufacturing process are cheap.